(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the function of European competencies in foreign language instruction plays a pivotal role in shaping language learning approaches across Europe. The role of European competencies in teaching foreign languages in Uzbekistan is a significant aspect of the country’s educational reform and modernization efforts. With globalization and international collaboration becoming increasingly vital, foreign language proficiency, particularly in European languages such as English, German, French, and Spanish, is seen as a key skill for students in Uzbekistan. European competencies, particularly the Common European Framework of Reference for Languages (CEFR), play a crucial role in shaping the language education system in Uzbekistan.